The Effect of Whistleblowing and Supervisory Professionalism on Fraud Prevention with Organizational Culture as Moderating Variable - Putu Anisa Gayatri; Putu Sukma Kurniawan; Made Aristia Prayudi (Research Horizon, 2026)
This research is motivated by the high potential and cases of fraud in Village Credit Institutions (Lembaga Perkreditan Desa/LPD) despite the implementation of various internal control mechanisms, so it is necessary to understand the factors that influence fraud prevention. This study aims to analyze the influence of the whistleblowing system and the professionalism of the supervisory board on fraud prevention, as well as to test the moderating role of organizational culture based on Tri Kaya Parisudha. The method used is a causal quantitative approach with a purposive sampling technique on 212 respondents. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that the whistleblowing system, the professionalism of the supervisory board, and organizational culture have a positive and significant effect on fraud prevention. However, organizational culture was not proven to moderate the relationship between the independent variables and fraud prevention. In conclusion, fraud prevention is more effectively achieved through a combination of formal mechanisms and a strong organizational culture, although the interaction of the two does not always significantly reinforce each other.